Humoral and cellular immune durability of different COVID-19 vaccine platforms following homologous/heterologous boosters: one-year post vaccination - Maaweya Awadalla; Halah Z. AlRawi; Rahaf A. Henawi; Fawziya Barnawi; Haitham Alkadi; Ahmed Alyami; Ammar Alsughayir; Alyazeed S. Alsaif; Ayman Mubarak; Wael Alturaiki; Bandar Alosaimi (Frontiers in Immunology)
IntroductionThe durability of Hybrid immunity induced by natural infection and/or COVID-19 vaccines and evidence supporting further booster vaccination are crucial factors for pandemic response, yet remain poorly understood.MethodsWe measured the durability of immune response and neutralizing capacity of antibodies following Homologous/Heterologous vaccination by mRNA-based vaccines (Pfizer-BioNTech BNT162b2) or (Moderna mRNA-1273) and viral vector-based vaccines (ChAdox1 nCoV-19-Oxford-AstraZeneca) in infected and non-infected patients. We also evaluated the long-lasting specific humoral IgG levels and T-cell immunity of the Memory CD8 cells.ResultsWe found that heterologous prime boosters led to significantly higher IgG antibody levels)9.09(than homologous boosters)5.236) one year after vaccination. We measured SARS-CoV-2 anti-S IgG antibodies and then assessed their neutralizing capacity to inhibit the receptor-binding domain (RBD) of the SARS-CoV-2 wild-type strain and omicron B.1.1.529/BA.2 variants from binding to the ACE2 receptors. The heterologous regiment demonstrated superior ACE2-binding inhibition and consistently had higher mean ACE2-receptor binding inhibition across all dose regimens without the need for further doses. The CD8+ T cells producing IFN-γ to various COVID-19 vaccine dose regimens were evaluated. We found that robust T cell mediated immune responses were preserved and largely induced by a heterogeneous vaccination eliciting a significantly higher CD8+ T cells IFN-γ response in 100% of vaccinees regardless of previous natural infection. Indeed, the difference between infected and naïve groups was less pronounced suggesting a reduced infection-related response.DiscussionAcross three layers of evidence, this study showed that heterologous vaccination provides longer-lasting immunity than homologous doses, regardless of prior natural infection.